Flow Path of the Carbonate Geothermal Water in Xiong’an New Area, North China: Constraints From 14C Dating and H-O Isotopes - Zhang, Baojian; Wang, Siqi; Kang, Fengxin; Li, Yanyan; Zhuo, Linyang; Gao, Jun; Yuan, Wenzhen; Xing, Yifei (Frontiers in Earth Science, 2022)
The geothermal water in carbonate rocks in Xiong'an New Area, China, is ancient. The sources of carbonate geothermal water are known but its flow path is not clear. To address this problem, we systematically collected data using 14C dating, 18O, and 2H in the Xiong'an New Area and surrounding carbonate geothermal water, Cenozoic sandstone geothermal water, Quaternary groundwater, and mountain spring water. The results revealed the following: (1) The 14C age of geothermal water in Cenozoic sandstone is older than that of geothermal water in carbonate rocks in the same section, indicating that the circulating runoff conditions of the carbonate reservoir geothermal water are better than conditions in the upper Cenozoic sandstone reservoir geothermal water. (2) The 14C age, deuterium excess parameter (d), and "18O drift" phenomenon are good indicators of the circulating runoff conditions and runoff path of geothermal water. Geothermal water in areas with young 14C age, a high value of d, and weak 18O drift phenomenon has good flow conditions. (3) Based on previous studies, the dominant flow path of regional carbonate geothermal water was identified: the geothermal water in Xiong'an New Area and surrounding karst is mainly recharged by the Taihang Mountains in the west and the Yanshan Mountains in the north. The Xushui-Wen'an structural transformation belt is a predominant flow channel for regional karst geothermal water. It is conducive to the recharge of karst water in the Taihang Mountains in the west and also receives recharge from the Cangxian Uplift in the east. The northeastern part of the Niutuozhen Uplift may be recharged by geothermal water from the carbonate rock in the eastern Cangxian Uplift through a small structural transformation belt. (4) Gaoyang Low Uplift, Rongcheng Uplift, and the southwestern part of Niutuozhen Uplift are the convergent areas of regional karst geothermal water. Thus, the 14C age is generally greater than 40,000 years. In addition, the value of d is small, and the phenomenon of 18O drift is obvious. The identification of the flow path of carbonate geothermal water provides a geothermal and geological basis for the scientific development of regional carbonate geothermal water.